Simulation and use of exchange wave fields to determine the azimuths of fractures - V.Yu. Roganov; V.V. Roganov (Геофизический журнал, 2012)
An efficient and stable method for synthesis of 3D-3C wavefields in a horizontally layered me-dium with differently oriented fractures is derived. The method enables either entire wavefield or a wavefield containing only waves of certain type for each layer to be obtained. In the process of wave generation, azimuthal-dependent NMO can be computed and applied to obtain azimuthal stacks.